Experimental and Statistical Study on the Properties of Basic Oxygen Furnace Slag and Ground Granulated Blast Furnace Slag Based Alkali-Activated Mortar - Ozkan, Hakan; Miyan, Nausad; Kabay, Nihat; Omur, Tarik (MDPI, 2023)
Basic oxygen furnace slag (BOFS) is a waste material generated during the steelmaking process and has the potential to harm both the environment and living organisms when disposed of in a landfill. However, the cementitious properties of BOFS might help in utilizing this waste as an alternative material in alkali-activated systems. Therefore, in this study, BOFS and blast furnace slag were activated with varying dosages of NaOH, and the fresh, physical, mechanical, and microstructural properties were determined along with statistical analysis to reach the optimal mix design. The test results showed that an increase in BOFS content decreased compressive and flexural strengths, whereas it slightly increased the water absorption and permeable pores of the tested mortar samples. On the contrary, the increase in NaOH molarity resulted in a denser microstructure, reduced water absorption and permeable pores, and improved mechanical properties. Statistically significant relationships were obtained through response surface methodology with optimal mix proportions, namely, (i) 24.61% BOFS and 7.74 M and (ii) 20.00% BOFS and 8.90 M, which maximize the BOFS content with lower molarity and improve the mechanical properties with lower water absorption and porosity, respectively. The proposed methodology maximizes the utilization of waste BOFS in alkali-activated systems and may promote environmental and economic benefits.
Keywords: basic oxygen furnace slag; alkali-activated mortar; response surface methodology; statistical analysis; sodium hydroxide; optimization; FLY-ASH; MECHANICAL-PROPERTIES; STEEL SLAG; BOF SLAG; GEOPOLYMER; METAKAOLIN; GLASS; VALORIZATION; PERFORMANCE; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering; Physics